Risk factors associated with self-reported musculoskeletal pain among short and long distance industrial gas delivery truck drivers. (October 2018) - Sekkay, Firdaous; Imbeau, Daniel; Chinniah, Yuvin; Dubé, Philippe-Antoine; de Marcellis-Warin, Nathalie; Beauregard, Nancy; Trépanier, Martin
Abstract: Aim: This study investigated and compared the associations between self-reported exposures to individual as well as work-related physical and psychosocial risk factors for musculoskeletal (MS) disorders and the prevalence of MS symptoms in different body areas among short- (P&D) and long-distance (Bulk delivery) truck drivers working for the same large gas delivery company in Canada. Methods: 123 truck drivers nationwide participated in this questionnaire-based cross-sectional study. Univariate and multivariate logistic regression analyses were performed. Results: 43.1% of drivers reported MS pain in at least one body area over the past 12 months and 26.8% over the past 7 days. Bulk drivers had a significantly higher prevalence of MS pain than P&D drivers for both periods. When P&D and Bulk drivers were pooled together, belonging to the Bulk subgroup emerged as the strongest factor for low back pain (OR = 8.45, p = 0.002), for shoulder pain (OR = 3.70, p = 0.027) and for MS pain in any body area (OR = 4.05, p = 0.006). In Bulk drivers "High effort-reward imbalance" was strongly associated with MS pain in any body area (OR = 6.47, p = 0.01), with shoulder pain (OR = 4.95, p = 0.016), and with low back pain (OR = 4.51, p = 0.02). In P&D drivers MS pain in any body area was strongly associated with "Working with hands above shoulders" (OR = 6.58, p = 0.009) and "Whole-body vibration" (OR = 5.48, p = 0.018), while shoulder pain was strongly associated with "Hand-arm vibration" (OR = 7.27, p = 0.041). Conclusions: Prevalence of MS pain was higher among industrial gas delivery truck drivers than in the general Quebec male worker population, and higher for Bulk drivers compared to P&D drivers. MS pain in Bulk drivers was mainly associated with psychosocial risk factors and lifestyle; MS pain in P&D drivers was mainly associated with physical risk factors. Highlights: Prevalence of musculoskeletal (MS) pain affecting the neck, shoulders and low back areas was higher in truck drivers than in the general worker population. Bulk (long-haul) delivery drivers reported significantly higher prevalence of MS pain in different body areas than P&D (short-haul) drivers. MS pain outcomes in Bulk drivers were mainly associated with psychosocial risk factors and lifestyle. MS pain outcomes in P&D drivers were mainly associated with physical risk factors and lifestyle.